Indicators of Multiple Intelligence Theory in the Karate Kid Movie (2010): English Education - Simanjuntak, Rutmintauli (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to analyze the indicators of Howard Gardner’s Multiple Intelligence Theory as represented in The Karate Kid movie (2010) and to examine their relevance to English education. Employing a qualitative descriptive research design, the study analyzes selected scenes, dialogues, character interactions, and narrative elements using Gardner’s Multiple Intelligence framework. The findings reveal that the movie portrays six types of intelligence: visual-spatial, bodily-kinesthetic, musical, interpersonal, intrapersonal, and naturalistic intelligence. These intelligences are manifested through physical training, social interactions, emotional development, environmental engagement, and auditory-visual elements embedded in the film. The results suggest that The Karate Kid functions as a multimodal instructional resource that aligns with learner-centered and differentiated approaches in English education. By integrating Multiple Intelligence Theory into film-based instruction, English teachers can design diverse learning activities that address varied learner strengths, enhance student engagement, and support holistic language development. This study contributes to the field of English education by highlighting the pedagogical value of films as instructional media and reinforcing the relevance of Multiple Intelligence Theory in contemporary language teaching practices.